If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) * 1 + -4 = 12 Reorder the terms: 2(1 + x) * 1 + -4 = 12 Reorder the terms for easier multiplication: 2 * 1(1 + x) + -4 = 12 Multiply 2 * 1 2(1 + x) + -4 = 12 (1 * 2 + x * 2) + -4 = 12 (2 + 2x) + -4 = 12 Reorder the terms: 2 + -4 + 2x = 12 Combine like terms: 2 + -4 = -2 -2 + 2x = 12 Solving -2 + 2x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 12 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 12 + 2 2x = 12 + 2 Combine like terms: 12 + 2 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 100=x(.02) | | k+-263.48=-381.09 | | 3y-15-8x-16=-2y-22 | | 5b+10=70 | | 7+9p=-110 | | -6x+4=10+8x | | 11x^2=13x+0 | | 40d^2+30=-14d^2 | | 100=x(.20) | | z=dxy | | (4x-6)3.5=119 | | 150*430=x | | x+-19.7=-17.48 | | 52=-6x-2 | | 21j-22j^2=-j^3 | | -3x-15=27-x | | 10-0.5s=20 | | 2x+3-(-4+5)=5x-2x+7 | | -10=5n-5 | | -3x-15=27-27 | | 48-y=36 | | 3r-16+7r=14 | | g-12=-1 | | x*x+8x=0 | | 11x-11+8x-8+30=180 | | 6+11=4t-7 | | 13-4(5x+1)=(7-5x)-15 | | 53-8383= | | 60=-10+3x | | 2(3)+3+-1(-4+5)= | | 14z-22=3(3z+11) | | -5x+7=2x-14 |